A Placebo-Controlled Double-Blind Randomized Trial with Individualized Homeopathic Treatment Using a Symptom Cluster Approach in Women with Premenstrual Syndrome - Yakir, Michal; Klein-Laansma, Christien T.; Kreitler, Shulamith; Brzezinski, Amnon; Oberbaum, Menachem; Vithoulkas, George; Bentwich, Zvi (Homeopathy, 2019)
Background In a double-blind placebo-controlled randomized trial with parallel groups, the efficacy of individually prescribed homeopathic medicines was evaluated in women with premenstrual syndrome (PMS).Methods In an outpatient department of a university clinic in Jerusalem, Israel (1996–1999), women with PMS, aged 18 to 50 years, entered a 2-month screening phase with prospective daily recording of premenstrual symptoms by the Menstrual Distress Questionnaire (MDQ). They were included after being diagnosed with PMS. A reproducible treatment protocol was used: women received a homeopathic prescription based on symptom clusters identified in a questionnaire. The symptoms were verified during a complementary, structured, interview. Only women whose symptoms matched the symptom profile of one of 14 pre-selected homeopathic medicines were included. Each participant was administered active medicine or placebo via random allocation. Primary outcome measures were differences in changes in mean daily premenstrual symptom (PM) scores by the MDQ. Analysis was by intention-to-treat.Results A total of 105 women were included: 49 were randomized to active medicine and 56 to placebo. Forty-three women in the active medicine group and 53 in the placebo group received the allocated intervention with at least one follow-up measurement and their data were analyzed. Significantly greater improvement of mean PM scores was measured in the active medicine group (0.443 [standard deviation, SD, 0.32] to 0.287 [SD, 0.20]) compared to placebo (0.426 [SD, 0.34] to 0.340 [SD, 0.39]); p = 0.043.Conclusions Individually prescribed homeopathic medicines were associated with significantly greater improvement of PM scores in women with PMS, compared to placebo. Replication, with larger sample size and other refinements, is recommended to confirm the efficacy of this treatment in other settings.
Keywords: premenstrual syndrome; randomized; double-blind; placebo-controlled trial; homeopathy; individualized; symptom cluster